Trivial role for NSMCE2 during in vitro proliferation and differentiation of male germline stem cells. Issue 3 (September 2017) - Zheng, Yi; Jongejan, Aldo; Mulder, Callista L; Mastenbroek, Sebastiaan; Repping, Sjoerd; Wang, Yinghua; Li, Jinsong; Hamer, Geert
Abstract : Spermatogenesis, starting with spermatogonial differentiation, is characterized by ongoing and dramatic alterations in composition and function of chromatin. Failure to maintain proper chromatin dynamics during spermatogenesis may lead to mutations, chromosomal aberrations or aneuploidies. When transmitted to the offspring, these can cause infertility or congenital malformations. The structural maintenance of chromosomes (SMC) 5/6 protein complex has recently been described to function in chromatin modeling and genomic integrity maintenance during spermatogonial differentiation and meiosis. Among the subunits of the SMC5/6 complex, non-SMC element 2 (NSMCE2) is an important small ubiquitin-related modifier (SUMO) ligase. NSMCE2 has been reported to be essential for mouse development, prevention of cancer and aging in adult mice and topological stress relief in human somatic cells. By using in vitro cultured primary mouse spermatogonial stem cells (SSCs), referred to as male germline stem (GS) cells, we investigated the function of NSMCE2 during spermatogonial proliferation and differentiation. We first optimized a protocol to generate genetically modified GS cell lines using CRISPR-Cas9 and generated an Nsmce2 −/− GS cell line. Using this Nsmce2 −/− GS cell line, we found that NSMCE2 was dispensable for proliferation, differentiation and topological stress relief in mouse GS cells. Moreover, RNA sequencing analysis demonstrated that the transcriptome was only minimally affected by the absence of NSMCE2. Only differential expression of Sgsm1 appeared highly significant, but with SGSM1 protein levels being unaffected without NSMCE2. Hence, despite the essential roles of NSMCE2 in somatic cells, chromatin integrity maintenance seems differentially regulated in the germline.